The Effect of Project Model through the Scientific Approach to the Ability to Prepare the Tools and Ingredients of Hydroponics Vegetables Cultivation of Deaf Students in Agriculture Skills Class SLB Negeri Balikpapan - Solikatun Napiah; Asri Wijiastuti; Sri Joeda Andajani (Department of Special Education, 2018)
The learning process of students with hearing impairment (deaf students) is adjusted to its characteristics. Agricultural skills are subjects that provide opportunities for students to gain experience in producing a product. This study aims to analyze the effect of project model through the scientific approach towards the ability to prepare tools and planting ingredients of hydroponic vegetables of Deaf students in farming skills class SLB Negeri Balikpapan. This research is Quantitative Pre-Experimental research with One Group Pretest-Posttest design. A pretest is performed prior to treatment. Posttest is performed to measure the effect of treatment. The number of samples in the study was 30 deaf students in SLB Negeri Balikpapan. The results showed that there was an increase in pretest-posttest average value as follows. 1) The project model obtained a pretest average of 47.83, post-test 79.17. 2) Ability to prepare the vegetable planting of hydroponics vegetables, the pretest average value was 48.30, and posttest was 80.27. 3) Scientific Approach, the average value of pretest was 49.40, posttest value was 78.07. 4) Ability to prepare planting vegetable hydroponics, the average value of pretest was 47.20, posttest was 80.33. Based on the data analysis, it can be concluded that: 1) The project model has the significant effect on the ability to prepare hydroponic vegetable apparatus of Deaf students in farming skill class of SLB Negeri Balikpapan. 2) The scientific approach has a significant effect on the ability to prepare hydroponic vegetable cultivation tools for Deaf students in farming skill class of SLB Negeri Balikpapan. 3) The project model has a significant effect on the ability to prepare the ingredients of Hydroponic vegetables of Deaf students in farming skill class SLB Negeri Balikpapan. 4) The scientific approach has a significant effect on the ability to prepare the ingredients of Hydroponic vegetables of Deaf students in the SLB Agricultural Skill class of Balikpapan State. 5) The project model through a scientific approach has a significant effect on the ability to prepare tools and ingredients of Hydroponic vegetables for Deaf students in farming skill class SLB Negeri Balikpapan.